Beyond Anthropomorphism: Social Presence in Human– AI Collaboration Processes - Siemon, Dominik; Elshan, Edona; de Vreede, Triparna; Ebel, Philipp; de Vreede, Gert‐Jan (Journal of Management Studies, 2026)
Abstract Artificial intelligence (AI) systems, evolving from reactive tools to proactive collaborators, reshape team dynamics in today's digital workplaces. Text‐based collaboration now frequently involves AI participants that perform tasks traditionally handled by humans, such as creative problem‐solving and decision‐making. This transition has been linked to changes in group dynamics, particularly in relation to social presence, which appears to shape the patterns of productivity and collaboration. We conducted three empirical studies on human–AI teams to investigate the relationship between social presence and willingness to depend on teammates, team‐oriented commitment, and motivation to contribute. Drawing on social presence theory and theory of planned behaviour, our results show that while social presence has a direct association with motivation to contribute, an equally important indirect pathway is associated with human factors like team‐oriented commitment and team members' willingness to depend on each other. We show that while social presence is significantly associated with behavioural intentions, greater AI familiarity and understandability are associated with a stronger relationship, raising questions about the sufficiency of relying solely on anthropomorphic features. Our study contributes to the understanding of human–AI collaboration in social presence research, highlighting the importance of considering social and interpersonal processes in hybrid teams. Our findings have managerial implications for organizations looking to adopt AI‐based systems for collaboration.